Membrane of Candida albicans as a target of berberine - Nataša Zorić (BMC Complementary and Alternative Medicine, 2017)
Abstract Background We investigated the mechanisms of anti-Candida action of isoquinoline alkaloid berberine, active constituent of medically important plants of Barberry species. Methods The effects on membrane, morphological transition, synthesis of ergosterol and the consequent changes in membrane permeability have been studied. Polarization and lipid peroxidation level of the membrane following berberine treatment have been addressed. Results Minimal inhibitory concentration (MIC) of berberine against C. albicans was 17.75 μg/mL. Cytotoxic effect of berberine was concentration dependent, and in sub-MIC concentrations inhibit morphological transition of C. albicans cells to its filamentous form. Results showed that berberine affects synthesis of membrane ergosterol dose-dependently and induces increased membrane permeability causing loss of intracellular material to the outer space (DNA/protein leakage). Berberine also caused membrane depolarization and lipid peroxidation of membrane constituents indicating its direct effect on the membrane. Moreover, ROS levels were also increased following berberine treatment indicating further the possibility of membrane damage. Conclusion Based on the obtained results it seems that berberine achieves its anti-Candida activity by affecting the cell membrane.